2019
DOI: 10.1017/ice.2019.191
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of matrix-assisted laser desorption ionization time-of-flight mass spectrometry for the management of inpatient pneumonia without additional antimicrobial stewardship support

Abstract: We assessed whether implementation of matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry without antimicrobial stewardship support would impact antimicrobial utilization and clinical outcomes in inpatient pneumonia. Implementation significantly reduced time to organism identification and time to optimal therapy but did not have a detectable impact on clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(1 reference statement)
1
2
0
Order By: Relevance
“…These findings are consistent with those reported by Perez-Lopez [34], emphasizing that rapid reporting contributes to the optimization of antibiotherapy. Our results align with studies conducted by de la Pedrosa [8], Osthoff [35,36], which describe the clinical impact of reducing the time for identification information and employ a similar methodology to our study. Notably, we report the antibiogram at 6-8 h after antimicrobial identification, while Osthoff [35], which takes the shortest of the three studies cited, takes 10 h. Other studies have demonstrated a statistically significant reduction in overall mortality and mortality related to infections with rapid diagnosis [37,38].…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with those reported by Perez-Lopez [34], emphasizing that rapid reporting contributes to the optimization of antibiotherapy. Our results align with studies conducted by de la Pedrosa [8], Osthoff [35,36], which describe the clinical impact of reducing the time for identification information and employ a similar methodology to our study. Notably, we report the antibiogram at 6-8 h after antimicrobial identification, while Osthoff [35], which takes the shortest of the three studies cited, takes 10 h. Other studies have demonstrated a statistically significant reduction in overall mortality and mortality related to infections with rapid diagnosis [37,38].…”
Section: Discussionsupporting
confidence: 90%
“…This finding illustrates an antimicrobial stewardship principle that occurs frequently in the literature: educational or informational resources make an impact when accompanied by patient-level antimicrobial stewardship team intervention. [10][11][12][13][14] More involvement of antimicrobial stewardship teams in provider-facing activities, such as audit and feedback and in-person presence on rounds ("handshake stewardship"), may be particularly effective. 2,[15][16][17][18][19] Physicians in our survey indicated that online general medical resources (eg, UpToDate, Wolters Kluwer) are the most frequently referenced when making antibiotic prescribing decisions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the technical cost is high and it can only be carried out in qualified units. 11 Therefore, early identification of the pathogenic bacteria responsible for pneumonia is particularly important.…”
Section: Introductionmentioning
confidence: 99%